2020
DOI: 10.3390/genes11060698
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species BAC Mapping Highlights Conservation of Chromosome Synteny across Dragon Lizards (Squamata: Agamidae)

Abstract: Dragon lizards (Squamata: Agamidae) comprise about 520 species in six subfamilies distributed across Asia, Australasia and Africa. Only five species are known to have sex chromosomes. All of them possess ZZ/ZW sex chromosomes, which are microchromosomes in four species from the subfamily Amphibolurinae, but much larger in Phrynocephalus vlangalii from the subfamily Agaminae. In most previous studies of these sex chromosomes, the focus has been on Australian species from the subfamily Amphibolurinae, but only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
(118 reference statements)
2
10
0
Order By: Relevance
“…Therefore, hybridisation of these BAC clones to study species metaphases would identify sex chromosome homologies. We also confirmed the locations of the 2 P. vitticeps clones, Pv03_L07 as previously mapped and sequenced by Ezaz et al [2013], Young et al [2013], Domaschenz et al [2015] and Alam et al [2020], and also keeping P. vitticeps female metaphase chromosomes as control during the experimentation. BAC Pv116_G15 contains the SF1 gene (Janine Deakin, pers.…”
Section: Repeat and Cross-species Gene Mappingsupporting
confidence: 84%
See 4 more Smart Citations
“…Therefore, hybridisation of these BAC clones to study species metaphases would identify sex chromosome homologies. We also confirmed the locations of the 2 P. vitticeps clones, Pv03_L07 as previously mapped and sequenced by Ezaz et al [2013], Young et al [2013], Domaschenz et al [2015] and Alam et al [2020], and also keeping P. vitticeps female metaphase chromosomes as control during the experimentation. BAC Pv116_G15 contains the SF1 gene (Janine Deakin, pers.…”
Section: Repeat and Cross-species Gene Mappingsupporting
confidence: 84%
“…In this study, BAC Pv116_G15 showed similar hybridisation patterns as Pv150_H19 (Fig. 8) by Alam et al [2020]. The sex microchromosomes of P. vitticeps were formed by a translocation of the region containing Pv03_ L07 sequences from the ancestral chromosome 2 [Matsubara et al, 2019].…”
Section: Chromosomal Rearrangements Revealed Through Fish Mappingsupporting
confidence: 73%
See 3 more Smart Citations